Changes in running economy at different intensities following downhill running - Chen, T. C.; Nosaka, K.; Lin, M.-J.; Chen, H.-L.; Wu, C.-J. (Journal of Sports Sciences, 2009)
In this study, we tested the hypothesis that running economy assessed at a high intensity [e.g. 90% maximal oxygen capacity (O2max)] would be affected more than at a lower intensity (e.g. 70%O2max) after downhill running. Fifteen untrained young men performed level running at 70, 80, and 90%O2max (5 min for each intensity) before and 2 and 5 days after a 30-min downhill run (gradient of -16%) at the intensity of their pre-determined 70%O2max. Oxygen consumption, minute ventilation, respiratory exchange ratio, heart rate, rating of perceived exertion, and blood lactate concentration were measured during the level runs together with kinematic measures (e.g. stride length and frequency) using high-speed video analysis. Downhill running resulted in significant (P < 0.05) decreases in maximal isometric strength of the knee extensors, the development of muscle soreness, and increases in plasma creatine kinase activity and myoglobin concentration, which lasted for 5 days after downhill running. Significant (P < 0.05) changes in all running economy and kinematic measures from baseline were evident at 2 and 5 days after downhill running at 80% and 90%O2max, but not at 70%O2max. These results suggest that running economy assessed at high intensity is affected more than at low intensity (lower than the lactate threshold).